15-15Ti(Si) austenitic steel: creep behaviour in hostile environment - Alessandra Strafella; Antonino Coglitore; Paride Fabbri; Elena Salernitano (Fracture and Structural Integrity)
This work aims at studying the creep behaviour of 15-15Ti(Si) austenitic steel, under uniaxial stress (range of 300-560 MPa), and its interaction with liquid lead. The steel was tested to verify its sensitivity to Liquid Metal Embrittlement (LME) and to simulate its behaviour in operating thermal and mechanical stress conditions of the IV generation Lead-cooled fast reactor. The experimental results permitted to plot the time-strain creep curve and the characteristic Norton-based curve, simulating the creep behaviour at all stress values. The comparison between the creep curves in air and in lead showed that the LME produces a decrease of creep-rupture time, a reduction of creep strain and then the loss of steel ductility. Moreover, the raw material and fracture surfaces were analyzed by Optical Microscope and Scanning Electron Microscope (SEM). SEM micrographs highlighted that lead changes both the mode and the type of specimen fracture. In addition, it was analyzed the lead action time, as the time after which the corrosion appears with macroscopic effects. Although some tests are still ongoing, it can be assumed that at high stresses, LME takes place after a long time of steel/lead contact while at low stresses, LME tends to prevail on creep effect.